2016
DOI: 10.1590/1982-0194201600091
|View full text |Cite
|
Sign up to set email alerts
|

Desfechos clínicos de pacientes com acidente vascular cerebral isquêmico após terapia trombolítica

Abstract: Objective: To analyze outcomes and associated factors in ischemic stroke patients submitted to thrombolytic therapy. Methods: This was a retrospective cohort study of ischemic stroke patients submitted to thrombolytic therapy. Comorbidities, neurologic deficits and time of thrombolysis were described. The chi-squared test was used to assess association among comorbidities, time of thrombolysis, and occurrence of hemorrhagic transformation. Results: There was a high frequency of comorbidities. Mean neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
1
0
11
Order By: Relevance
“…This research project showed that two preventable complications—pneumonia and urinary tract infection—and one neurological complication significantly increase the length of hospital stay in a stroke unit after the first-ever ischemic stroke or TIA. Previous studies demonstrated that pneumonia and urinary tract infection were the most common clinical complications after an ischemic stroke, increasing morbidity and mortality 21-23 . The frequency of these complications in the study population was very similar to previous published studies; pneumonia between 10.6% and 21.2% 6,24-25 , and urinary tract infection between 3.2% and 5.0% 6,24 .…”
Section: Discussionmentioning
confidence: 99%
“…This research project showed that two preventable complications—pneumonia and urinary tract infection—and one neurological complication significantly increase the length of hospital stay in a stroke unit after the first-ever ischemic stroke or TIA. Previous studies demonstrated that pneumonia and urinary tract infection were the most common clinical complications after an ischemic stroke, increasing morbidity and mortality 21-23 . The frequency of these complications in the study population was very similar to previous published studies; pneumonia between 10.6% and 21.2% 6,24-25 , and urinary tract infection between 3.2% and 5.0% 6,24 .…”
Section: Discussionmentioning
confidence: 99%
“…De entre os indicadores de qualidade salientamos os outcomes obtidos em termos neurológicos e em termos funcionais. À semelhança de outros estudos, comparando vários momentos verifica-se uma evolução neurológica e funcional positiva (23,(25)(26) . No que respeita à NIHSS obtivemos uma média de 3.6 pontos à alta e 2.8 pontos na avaliação da consulta.…”
Section: à Altaunclassified
“…No entanto a distribuição é semelhante, isto é, predominam os doentes com um grau de comprometimento neurológico leve. (25)(26) No que concerne ao IBm, verificamos um valor médio à alta semelhante a outros estudos, mas ligeiramente superior na avaliação da consulta. Concretizando a comparação com o estudo de Nunes (2016), os valores médios do IBm situavam-se nos 75,64 pontos e 78,39 pontos, à alta e aos 30 dias respetivamente, enquanto no presente estudo os valores situam-se nos 74 pontos e 84 pontos nos dois momentos (26) .…”
Section: à Altaunclassified
“…O AVEi é responsável por 85% dos casos de Acidente Vascular Encefálico (AVE) 2 , e em sua maioria ocorre oclusão tromboembólica na área arterial correspondente à manifestação neurológica 3 . Aproximadamente 10-14% do AVEi ocorre em adultos jovens e a sua incidência nessa população varia de 7 a 15 por cada 100.000 indivíduos/ano 4 .…”
unclassified
“…Data da recepção: 27 de outubro de 2017 Data de aceitação: 15 de dezembro de 20172 Enfermagem pela Universidade Estadual do Sudoeste da Bahia, Jequié, Bahia, Brasil. Correio eletrônico: edison.vitorio@gmail.com3 Enfermagem pela Universidade Estadual do Sudoeste da Bahia, Jequié, Bahia, Brasil. Correio eletrônico: marianasoledade09@gmail.com4 Enfermagem pela Universidade Estadual do Sudoeste da Bahia, Jequié, Bahia, Brasil.…”
unclassified